Genomic Epidemiology and Antimicrobial Susceptibility Profile of Enterotoxigenic Escherichia coli From Outpatients With Diarrhea in Shenzhen, China, 2015–2020 - Yang, Chao; Li, Yinghui; Zuo, Le; Jiang, Min; Zhang, Xianglilan; Xie, Li; Luo, Miaomiao; She, Yiying; Wang, Lei; Jiang, Yixiang; Wu, Shuang; Cai, Rui; et al. (Frontiers in Microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) is the leading cause of severe diarrhea in children and the most common cause of diarrhea in travelers. However, most ETEC infections in Shenzhen, China were from indigenous adults. In this study, we characterized 106 ETEC isolates from indigenous outpatients with diarrhea (77% were adults aged >20 years) in Shenzhen between 2015 and 2020 by whole-genome sequencing and antimicrobial susceptibility testing. Shenzhen ETEC isolates showed a remarkable high diversity, which belonged to four E. coli phylogroups (A: 71%, B1: 13%, E: 10%, D: 6%) and 15 ETEC lineages, with L11 (25%, O159:H34, ST218/ST3153), novel L2/4 (21%, O6:H16, ST48) and L4 (15%, O25:H16, ST1491) being major lineages. Heat-stable toxin (ST) was most prevalent (76%, STh: 60% STp: 16%), followed by heat-labile toxin (LT, 17%) and ST+LT (7%). One or multiple colonization factors (CFs) were identified in 68 (64%) isolates, with the common CFs being CS21 (48%) and CS6 (34%). Antimicrobial resistance mutation/gene profiles of genomes were concordant with the phenotype testing results of 52 representative isolates, which revealed high resistance rate to nalidixic acid (71%), ampicillin (69%) and ampicillin/sulbactam (46%), and demonstrated that the novel L2/4 was a multidrug resistant lineage. This study provides novel insight into the genomic epidemiology and antimicrobial susceptibility profile of ETEC infections in indigenous adults for the first time, which further improves our understanding on ETEC epidemiology and has implications for the development of vaccine and future surveillance and prevention of ETEC infections.